ENVIRONMANTAL CONFLICTS IN THE COASTAL ZONE OF HAI PHONG CITY - Trang, Cao Thi Thu; Lan, Tran Dinh; Nghi, Duong Thanh; Huong, Do Thi Thu (Vietnam Journal of Marine Science and Technology, 2012)
Three outstanding conflicts in the coastal zone of Hai Phong had been identified and analysed. They are conflict between port development (include widen Hai Phong port and building new port Lach Huyen) and biodiversity protection; conflict between industrial development and environmental protection in Hai Phong; and development between torism development and environmental protection in Cat Ba Island. All of them are conflicts between economic development and environment protection. For typology, these are chronic and related to the change of natural resources; the cases of Hai Phong port development and industrial development in Hai Phong city conflicts are also anticipation; for stages, almost ones are at conflict formation and conflict management. For ranking, the conflict related to port development is urgency, conflict related to industrial development is critically and the last one is duration.